A Decade of Regulation 650/2012: The Role of the European Certificate of Succession in Standardisation, Evidentiary Effects and Land-Register Entries - Ivanc, Tjaša (65 pravne znanosti v Mariboru, 2026)
This chapter examines the European Certificate of Succession (ECS) as an instrument for cross-border succession, enabling heirs, legatees, and executors to prove their status. It analyses the relationship between the ECS’s evidentiary effects and lex rei sitae in registrations: rights in rem and the formalities and effects of entries remain governed by the law of the register state (Arts 1(2)(k),(l), 69(5)). An ECS may suffice for registration in another Member State if its content matches the intended use and the property is identified; the CJEU in case R.J.R. v Registrų centras VĮ confirms that registries may refuse registration where immovables are not identified. Under Art. 227.e of the Slovenian Inheritance Act, a foreign ECS has the nature of a certificate of inheritance and is a basis for entry under the Land Register Act. Digitalisation – Regulation 2023/2844, Regulation 910/2014 (eIDAS 2) and the European Digital Identity Wallets (EUDI Wallet) – enables verifiable e-copies and machine-readable annexes, speeding up entries and strengthening trust.